Characteristics of management accounting systems in portuguese industry - Ussman, Ana Maria (2015)
This article summarises the results of a survey on the accounting systems implemented in large Portuguese manufacturing firms. The literature review was used to define the hypotheses of the study and the analysis of data characterises the state of art of management accounting systems of the surveyed firms. The data was gathered by postal questionnaire. The study shows a preference for simple criteria in costing inventory-flow and in cost allocation methods for determining the cost of the product. The major conclusion is that simplicity is preferred over technical and statistical rigor.